(untitled) (Research, Society and Development, 2021)
Lipids play a fundamental role in humans, being a macronutrient transported by lipoproteins within the body. The appearance of non-communicable chronic diseases is increasing every day, being one of the main causes of morbidity, disability and mortality in Western societies. For a long time this macronutrient has been associated with the development and progression of such diseases. The objective of this work is to search for a compilation of the literature on the benefits of the individual components of dairy fats for human health. It can be concluded from the works reported that there is an increasing consensus that dairy fats are of great complexity with regard to their composition, having high nutritional value and bioactivity, which can also help in weight loss and prevention of a series of diseases such as cancers, metabolic syndrome, antidiabetic properties, modulation of the intestinal microbiota, hypertension, obesity, prevention of allergies and asthma, among others.